Efektivitas Pelayanan Pada Mal Pelayanan Publik Kota Tangerang Selatan - Salsabilla Putri Rahmadhany; Evi Satispi (Jurnal Media Administrasi, 2024)
Public services organized by the state aim to fulfill the needs of citizens. Therefore, the government has an obligation to improve the quality of services provided. The South Tangerang City Government made innovations in organizing services through the construction of the Public Service Mall. This research aims to find out how the effectiveness of services at the South Tangerang City Public Service Mall. The research method used is descriptive qualitative. The results of this study indicate that the effectiveness of services at the South Tangerang City Public Service Mall based on the theory of Ridwan and Sudrajat (2009: 103) has been running quite effectively, but there are still some obstacles in the implementation of these services.